2013
DOI: 10.1177/2048872613484686
|View full text |Cite
|
Sign up to set email alerts
|

Invasive mechanical ventilation in acute coronary syndromes in the era of percutaneous coronary intervention

Abstract: Percutaneous coronary intervention (PCI) has emerged during the last decades as one of the most important therapeutic tools in patients with acute coronary syndromes (ACS). 1 PCI improves the prognosis of patients with ACS, 2,3 reducing the incidence of ischaemic complications and heart failure, 4 especially in those patients at higher risk, 5-7 thus potentially changing the need for invasive mechanical ventilation (IMV) in this clinical scenario. Little information is available regarding the profile of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“…In contrast to previous studies of patients requiring mechanical ventilation or suffering from cardiogenic shock following complicated myocardial infarction, our study reviewed consecutive patients admitted to ICU exclusively via the PPCI pathway [ 8 13 , 16 , 17 ]. This included both patients who required mechanical ventilation and those who did not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to previous studies of patients requiring mechanical ventilation or suffering from cardiogenic shock following complicated myocardial infarction, our study reviewed consecutive patients admitted to ICU exclusively via the PPCI pathway [ 8 13 , 16 , 17 ]. This included both patients who required mechanical ventilation and those who did not.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the pervasiveness of PPCI in the management of STEMI and the appropriate use of CCU care, there remains a small proportion of patients that become critically ill and require advanced life support modalities post-PPCI, such as mechanical ventilation or vasoactive therapy that may only be provided within the intensive care unit (ICU). Historically, patients with a complicated myocardial infarction requiring mechanical ventilation have been associated with high rates of morbidity and mortality [ 8 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of the remaining 48 articles, 43 were excluded because of poorly defined IMV use or unreported mortality data. Therefore, five studies were selected for detailed review [ 24 - 28 ], and the study by Kontoyannis et al [ 24 ] was further excluded due to the patient group being small (10 treated with IMV) and the lack of early emergency revascularization therapy by PCI. Finally, four studies in total were included for meta-analysis, and all data from patients treated with IMV were extracted [ 25 - 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, five studies were selected for detailed review [24][25][26][27][28], and the study by Kontoyannis et al [24] was further excluded due to the patient group being small (10 treated with IMV) and the lack of early emergency revascularization therapy by PCI. Finally, four studies in total were included for meta-analysis, and all data from patients treated with IMV were extracted [25][26][27][28]. All four studies reported in-hospital mortality rate, while only one study reported 28-day mortality rate [25].…”
Section: Meta-analysis Of Pci + Imv + Partial Iabp In the Treatment Omentioning
confidence: 99%
“…2). Some data suggest that the requirement of mechanical ventilation in patient with acute coronary syndromes, as signs of higher acuity, are burden by higher mortality [39].…”
Section: Noninvasive Ventilation In Cardiogenic Shockmentioning
confidence: 99%